THE FIGURE OF MAHDI IN SUFI ESCHATOLOGY OF DAGESTAN: HISTORICAL AND CONTEMPORARY CONTEXT - Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2025)
This article explores Sufi conceptions of Mahdi in the historical context of Dagestan and analyzes their current state. In Dagestani Sufism, the figure of Mahdi is an integral part of eschatological beliefs, centered around the expectation of the imminent arrival of the savior of the Islamic world and the understanding of one’s role in this process. The article traces the development of these teachings in detail: from their dissemination in the works of Middle Eastern Sufis to their adaptation in the writings of Dagestani ‘ulama and Sufis. These eschatological ideas entered Dagestan in the second half of the 18th century and, evolving over two centuries, became a significant part of regional Sufism. It has been established that after the end of the Caucasian War, some ‘ulama loyal to the new imperial authority utilized these beliefs to counteract anti-colonial sentiments. Apocalyptic expectations and related ideas about Mahdi were revived at the beginning of each Islamic century, as well as during times of political and economic crises. In the post-Soviet period, against the backdrop of the collapse of the USSR and the revival of Islam in national republics, the figure of Mahdi gained special significance for Dagestani Sufis. In the contemporary era, Sufi conceptions of Mahdi not only remain relevant but also receive new impetus for development. In Dagestan, they manifest in a specific form—through the concept of the deputy (na’ib) of Mahdi and the recognition of a special mission for his followers. This phenomenon in Dagestan can be seen as a consequence of the reconciliation process between the state and Sufism in the post-Soviet period.
Keywords: Sufi Mahdism; Mahdi; al-Sha‘rani; Ibn ‘Arabi; Sa‘id-Afandi al-Chirkawi; Mufti of Dagestan; Muftiate; apocalypse; Islamic eschatology; history of Islam in Dagestan; Sufism in Dagestan